Interpenetrating Polymer Network Hydrogels Based on Gelatin and PVA by Biocompatible Approaches: Synthesis and Characterization - Eltjani-Eltahir Hago; Xinsong Li (Advances in Materials Science and Engineering)
In this work, a new approach was introduced to prepare interpenetrating polymer network PVA/GE hydrogels by cross-linking of various concentration gelatin in the presence of transglutaminase enzyme by using the freezing-thawing cycles technique. The effects of freezing-thawing cycles on the properties of morphological characterization, gel fraction, swelling, mechanical, and MTT assay were investigated. The IPN PVA/GE hydrogels showed excellent physical and mechanical Properties. MTT assay data and the fibroblasts culture also showed excellent biocompatibility and good proliferation. This indicates that the IPN hydrogels are stable enough for various biomedical applications.